2018
DOI: 10.1002/jcp.26412
|View full text |Cite
|
Sign up to set email alerts
|

Potential neuroprotective effect of androst‐5‐ene‐3β, 17β‐diol (ADIOL) on the striatum, and substantia nigra in Parkinson's disease rat model

Abstract: Parkinson's disease (PD) is a progressive neurodegenerative disorder with behavioral and motor abnormalities. Androst-5-ene-3β, 17β-diol (ADIOL), an estrogen receptor (ER) β agonist, was found to mediate a transrepressive mechanism that selectively modulates the extent of neuroinflammation and, in turn, neurodegeneration. In consensus, ERβ polymorphism was more frequently detected in early-onset PD patients. Thus, in an approach to elucidate the role of ERβ agonists on PD, our study was designed to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 55 publications
0
5
0
1
Order By: Relevance
“…Similar effects could not be observed with a selective synthetic ERβ agonist in these studies. However, another study found that the endogenously produced 5-androstene-3β, 17β-diol, an ERβ agonist, protects against neuroinflammation in the rotenone-induced rat model of PD [ 143 ], suggesting that type of PD model and type of selective ER modulators may influence the neuroprotective readouts. Furthermore, a polymorphism in the human ERβ gene was more common in both sexes of early-onset PD patients compared with late-onset patients [ 144 ], whereas ERα polymorphisms appear to not be associated with PD [ 145 ].…”
Section: Estrogen Receptors In Neurodegenerationmentioning
confidence: 99%
“…Similar effects could not be observed with a selective synthetic ERβ agonist in these studies. However, another study found that the endogenously produced 5-androstene-3β, 17β-diol, an ERβ agonist, protects against neuroinflammation in the rotenone-induced rat model of PD [ 143 ], suggesting that type of PD model and type of selective ER modulators may influence the neuroprotective readouts. Furthermore, a polymorphism in the human ERβ gene was more common in both sexes of early-onset PD patients compared with late-onset patients [ 144 ], whereas ERα polymorphisms appear to not be associated with PD [ 145 ].…”
Section: Estrogen Receptors In Neurodegenerationmentioning
confidence: 99%
“…As for androstane steroids, DHEA treatment rescued depleted TH-positive neurons and recovered ERK phosphorylation [467]. ADIOL ameliorated rotenone-induced elevation of NF-κB and expression of iNOS and IL-6 [311]. Taken together, these studies suggest a potential protective role of pregnane and androstane steroids in PD pathology, in part, through neuroimmune regulation.…”
Section: Neurodegenerative Diseasesmentioning
confidence: 71%
“…It serves as a selective modulator of estrogen receptors (ER), effectively suppressing inflammatory reactions in microglia and astrocytes [108]. Studies by Salama et al revealed that ADIOL reduces NF-kB levels in both the striatal and nigral regions of a rat model with rotenone-induced Parkinson's disease (PD) [311]. Additionally, ADIOL promotes the production of the anti-inflammatory cytokines IL-4 and IFN-γ in experimental autoimmune encephalomyelitis, mitigating axonal damage resulting from demyelination by shifting microglial polarization toward a reparative state [312,313].…”
Section: Mechanisms Of Action Of Androstane Neuroactive Steroids On T...mentioning
confidence: 99%
“…Apart from regulating the PD disease-associated PARK genes ERβ could maintain dopamine levels, and reduce neuroinflammation and ROS generation. 131 The knockout of ERβ from the midbrain precursor cells was associated with decreased expression of engrailed homeobox 1 and 2 (EN1 and EN2), and orthodenticle homeobox 2 (OTX2) genes. EN1 and EN2 are essential in the development and maintenance of mesencephalic dopaminergic neurons.…”
Section: Other Neuroprotective Effects Of Erβ In Pdmentioning
confidence: 99%
“…The mechanisms by which estrogen confers neuroprotective effects in PD are diverse. Apart from regulating the PD disease‐associated PARK genes ERβ could maintain dopamine levels, and reduce neuroinflammation and ROS generation 131 . The knockout of ERβ from the midbrain precursor cells was associated with decreased expression of engrailed homeobox 1 and 2 (EN1 and EN2), and orthodenticle homeobox 2 (OTX2) genes.…”
Section: Therapeutic Benefits Of Selective Erβ Activation In Pdmentioning
confidence: 99%